Performance evaluation of solar photo voltaic pumping system - Singh, A K; Pande, P C (Journal of Agricultural Engineering, 2000)
Head discharge characteristics curve for a solar photo voltaic pump has been developed. The performance of the system has been evaluated in terms of overall systems efficiency with regard to different sets of head and discharge rates. The overall system efficiency varied from 2 to 4 per cent. The total head and discharge rate corresponding to maximum efficiency were found to be 10 m and 3.0 1ps respectively. The cost of pumping is estimated to be Rs 1.42 mÂ¯Â³.